(untitled) (Bangladesh Journal of Medicine, 2020)
The presentation of Rheumatoid arthritis (RA) combined with a second rheumatological disorder thatis, different RA overlap syndromes are frequently encountered in clinical practice. But RA-vasculitisoverlaps are relatively rare. This paper presents a case of Rheumatoid arthritis and Granulomatosiswith polyangiitis (Wegener granulomatosis) overlap syndrome which is first of its kind reported from Bangladesh. Bangladesh J Medicine July 2020; 31(2) : 114-119